2018
DOI: 10.1039/c8gc00268a
|View full text |Cite
|
Sign up to set email alerts
|

Covalent triazine framework catalytic oxidative cleavage of lignin models and organosolv lignin

Abstract: CTFs were used as effective metal-free catalysts for the oxidative cleavage of lignin model compounds and organosolv lignin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 67 publications
4
45
0
Order By: Relevance
“…8). Firstly, with the assistance of K 2 CO 3 , 1-phenylethane-1,2-diol (1a) was oxidized to the 2-hydroxy-1-phenylethanone (5a) (or the tautomer 5b as well) by the active species generated from the activation of oxygen by the Co-based catalyst [36][37][38][39][40] . Then, there are two possible reaction pathways for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…8). Firstly, with the assistance of K 2 CO 3 , 1-phenylethane-1,2-diol (1a) was oxidized to the 2-hydroxy-1-phenylethanone (5a) (or the tautomer 5b as well) by the active species generated from the activation of oxygen by the Co-based catalyst [36][37][38][39][40] . Then, there are two possible reaction pathways for this reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Thec orresponding aromatic esters were obtained in good to moderate yields.Specifically,the catalytic system can also effectively oxidize cleavage of complex lignin models with Cg-OH into corresponding esters in moderate yields.H owever,t he lower yield of the desired phenolic compounds was afforded (10-30 %y ield), possibly due to over-oxidization and/or the formation of low polymer.T his observed result is in accordance with previous reports on the oxidative cleavage of lignin model compounds. [18][19][20][21][22][23] To better elucidate the mechanism of the oxidative cleavage of secondary alcohols to esters,wefirst implemented ar adical inhibition experiments to determine whether the reaction involves free radicals.T he results showed that the radical scavengers 2,6-di-tertbutyl-4-methylphenol (BHT) or (2,2,6,6-tetramethyl-1-piperidinyloxy (TEMPO) had no effect on the formation of target products (Supporting Information, Scheme S1), thus suggesting that the radical reaction process can be ruled out.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…They can be reductive or employ redox-neutral catalysis, 8 acid- or base-catalysis, 9 and oxidative catalysis. 10 For oxidative transformations, it was found that α-oxidation of the secondary alcohol group in the β-O-4 motif in lignin or in similar lignin model compounds decreased the bond strength of the neighboring C–C and C–O bonds. 11 Stephenson and co-workers validated this observation by density functional theory calculations with respect to the cleavage of adjacent C–O bond in β-O-4 model systems (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%